Technology and practice of intelligent governance for financial data security - Peng HOU; Zhixin LI; Fei ZHANG; Xu SUN; Dan CHEN; Yihao CUI; Hanbing ZHANG; Yinan JIN; Hongfeng CHAI (网络与信息安全学报)
In the “14th Five-Year Plan” era, the digitization of the financial industry has entered a phase of deepening and high-quality development.Strengthening Financial Data Security Governance (FDSG) and protecting financial data security have become an objective need and essential requirements for developing national economic security.FDSG utilizes data governance measures as a fundamental tool with a focus on sensitive data to ensure the comprehensive security of the entire lifecycle of financial data.It aims to promote data circulation among financial institutions, activate data value, and facilitate market-oriented allocation of financial data elements.FDSG is increasingly intertwined with big data, artificial intelligence, cloud computing, and blockchain technologies, transforming traditional data security governance into intelligent governance and accelerating the evolution of FDSG towards automation, intelligence, efficiency, and precision.FDSG’s essence, scope, and governance framework were introduced, and the core concepts and critical supporting technologies for the intellectual development of FDSG were elaborated, outlining the roadmap for intelligent governance.With consideration of FDSG’s demands and characteristics of intelligent technologies, vital directions for the practical application of intelligent technologies in FDSG were outlined, including data classification, data traceability, content control, privacy protection, and data twinning.Examples of current intelligent governance practices in banking, securities, and insurance industries were provided.Policy recommendations were proposed in the paper to promote the standardized and intelligent development of FDSG in China’s new era, aiming to foster the sustainable development of financial institutions and industries and ensure a healthy and secure environment for the future.